One More Attempt by the US Administration in Bosnia and Herzegovina: Constitutional Reform of the Federation of Bosnia and Herzegovina—Mission Impossible or Back to the Future?. Issue 4 (4th July 2017) - Begić, Zlatan
Abstract: The Constitution of the Federation of Bosnia and Herzegovina is a part of the Washington Peace Agreement which was the first step in establishing the sustainable peace in Bosnia and Herzegovina. This Constitution established a complex constitutional arrangement of this entity, which consists of 10 federal units—cantons. In the post-war period it turned out that the Constitution of the Federation of BH contains a number of inconsistent, contradictory and vague solutions that seriously affect the functionality of the entire system of government. This is particularly evident in the European integration process, which requires the effective fulfillment of the commitments derived from this process. Given the above, the US Ambassador to Bosnia and Herzegovina Mr. Patrick Moon formed an independent Expert Group consisting of local experts, with the aim to propose concrete recommendations to establish a more efficient, more functional and cheaper system of government in the interest of citizens. This paper provides analysis of the most important system problems in the functioning of government in the Federation of BH and the solutions that, within the Draft of the new Constitution of the Federation of BH, were offered by the Expert Group in the realization of the set project task.